The Culture of Gotong Royal Work as a Manifestation of Collective Citizenship with Social Concern - Hajuan, Muhammad Akbar; Retta, Lensi Megah; Mansur, Ali (Edumedia Solution, 2025)
The culture of mutual cooperation can foster social attitudes that are manifested in the form of actions or behavior in groups. With the culture of mutual cooperation, people are able to work together in solving various problems and also lightening the burden of fellow citizens. Through the phenomenological research method, researchers will know and easily understand the object of research. Researchers use data collection techniques by means of interviews, observations, and documentation. Interviews are data collection techniques by asking questions to informants or submitting a number of questions verbally to research subjects. The results of the study indicate that the culture of mutual cooperation marriage requires thought, energy, space and time to build moral values in society. The elements of mutual cooperation culture are very urgently expressed in social systems and traditions. The culture of mutual cooperation can process interactions and build moral values of the younger generation by adhering to the basic values of Pancasila as a manifestation of equality of fate.